Ocorrência de ouro nos depósitos pliocénicos da região de Cruz de Pau (Seixal) - Salgueiro, R. (2010)
Recently had been discovery, in the area of the construction of the Carla Sacramento Athletics Stadium at Cruz de Pau (Seixal), a set of stopes and wells with characteristics of ancient Roman mining activities. The old mining works are incised in pliocene sandy formations with conglomeratic facies, where four preliminary samples were collected in a coarser level with subrounded pebbles. The heavy minerais of those samples were studied in accordance with the Heavy Mineral Concentrate Laboratory of the IGM. The previously mentioned facies has interesting gold percentages and the presence of grey (nodular) and classic monazite, xenotime, cassiterite, spinels s.l., ilmenite and rutile. The morphology of the gold grains as well as the heavy minerals shows two phases of transport; an initial fluvial phase and a secondary aeolian phase influenced their concentracion. The high percentage of toroid grains showing evidence of wind ablation, suggests that this was the main factor for reconcentration of the gold. The amount of gold particles obtained in the concentrates is considerable and in one sample, a grade of 3.2 ppm was calculated. The samples also have been analysed for Au + 34 elements by INAA and ICP-MS, the results of which show similar grades as previously obtained.